The relationship between doctors, patients and the law in North American and British literature - Kennedy, Victor (Medicine, law & society, 2016)
In common law jurisdictions today, the relationship between doctors and patients is generally considered to be a private one (Dorr Goold and Lipkin Jr., 1999). Like most professions, doctors are governed to a large extent by professional associations with their own Codes of Ethics. To practice medicine in the United States, Canada, or Britain, doctors must be licensed by their local Board or College1 . Government control of doctor-patient relationships is generally limited to funding, but in a few areas, in particular, those that are considered to be matters of public morality or ethics, criminal statutes can apply. Historically, reproductive rights have often fallen under state control. This paper will compare fictional representations of state interference with reproductive rights in three science-fiction dystopias, Margaret Atwood's The Handmaid's Tale (Atwood, 1985), P.D. James's Children of Men (James, 1992), and Harlan Ellison's "A Boy and His Dog" (Ellison, 1969), and examine the real-world situations and concerns that these stories comment upon.
Keywords: American literature; ameriška književnost; angleška književnost; health care; pacienti; pravna ureditev; zdravniki; zdravstvo